RAMAN SPECTRA AND LATTICE-DYNAMICAL CALCULATIONS OF NATROLITE - Goryainov S.V.; Smirnov M.B. (My University, 2001)
Polarized single-crystal Raman scattering and powder infrared absorption spectra of Fdd2 orthorhombic natural natrolite (Na-1.88 K-0.02 Ca-0.04 )[Al-1.96 Si-3.03 O-10].2.03 H2O from Khibiny, Kola peninsula, were measured. Using short-range models, lattice-dynamical calculations were performed for an idealized natrolite structure Na-4[Al4Si6O20]4H(2)O containing 46 atoms in the primitive unit cell (Z = 2). By varying the valence force constants, the calculated frequencies in the Raman and IR spectra were fitted to the observed frequencies. On considering their calculated intensities as well, nearly all the observed bands (especially those corresponding to the A(1) modes) could be unambiguously assigned and interpreted. The external vibrations of H2O could be correctly assigned using deuterated samples. The strongest Raman band at 534 cm(-1) corresponds to a breathing mode of the four-membered aluminosilicate ring. The calculated bulk modulus (52.7 GPa at zero pressure) is close to the experimental value of 47 +/- 6 GPa. The natrolite structure has some advantages upon other zeolites to understand the amorphization mechanism, because samples of this mineral surrounded by a non-penetrating medium show no crystal phase transitions with increasing, pressure. Lattice energy minimization calculated with variable unit-cell dimensions shows the crystal structure to become unstable at about 5.5 GPa, thereby apparently explaining the amorphization process at 4-7 GPa. This instability is connected with shear acoustic modes coupled with soft internal framework vibrations.
Keywords: Raman spectra; IR spectrum; natrolite; lattice dynamics; vibrational modes; phonon dispersion curves